Determinants of Audit Opinion Accuracy: The Roles of Auditor Independence and Professionalism Evidence From West Java and Jakarta - Satria, Muhammad Rizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
Inaccurate audit opinions in both public and private sectors indicate potential weaknesses in auditor independence and professionalism. This study investigates the effects of auditor independence and professionalism on audit opinion accuracy. A quantitative approach was employed using primary data collected from 142 auditors working in public accounting firms across West Java and DKI Jakarta, Indonesia. The data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both auditor independence and professionalism have significant positive effects on audit opinion accuracy. However, professionalism exerts a stronger influence than independence, indicating that auditors' competence, professional judgement, and ethical behaviour play a more prominent role in producing accurate audit opinions. The structural model demonstrates moderate explanatory power and strong predictive relevance, as confirmed by PLSpredict analysis. Furthermore, Multi-Group Analysis (MGA) indicates no significant regional differences, suggesting that the structural relationships are stable across both regions. The findings underscore the importance of strengthening auditors' professionalism and ethical competence to improve audit quality and reinforce public confidence in financial reporting.